Beauty Premium and Marriage Premium in Search Equilibrium: Theory and Empirical Test - Roberto Bonilla; Francis Kiraly; John Wildman (Center for Economic Studies and ifo Institute (CESifo), 2015)
We propose a theoretical explanation for the so-called beauty premium. Our explanation is based entirely on search frictions and the fact that physical appearance plays an important role in attracting a marriage partner. We analyse the interaction between frictional labour and marriage markets and establish the existence of a search equilibrium characterised by male wage differentials. The equilibrium may also display the marriage premium, predicted to be lower among attractive men. The link between beauty premium and marriage premium provides a falsification test of the model. We carry out the empirical analysis and conclude that we cannot refute the theory.
Keywords: D83; J12; J31; 330; search; frictional labour market; frictional marriage market; beauty premium; marriage premium